THE IMPORTANCE OF EOLIAN ABRASION IN SUPERMATURE QUARTZ SANDSTONES AND THE PARADOX OF WEATHERING ON VEGETATION-FREE LANDSCAPES - Dott R.H.Jr. (My University, 2003)
Pure quartz arenites are especially characteristic of lower Paleozoic and Proterozoic strata deposited in nonorogenic settings. A century-long debate over the origin of these remarkably pure sandstones has remained unresolved, largely because they seem nonactualistic. The much greater importance of wind and fluvial processes prior to the Silurian appearance of macroscopic vegetation supported a physical origin, but it is now clear that both multicycling and intense chemical weathering can produce them. Multicycling seemed essential to account for their extreme textural maturity, with the exceptional rounding of many examples pointing to important colian abrasion. Other attributes such as evidences of mixed sources, upward maturation, association with major unconformities, and an inverse relationship between labile grain content and grain size also were consistent with recycling. A single-cycle origin proven in the modern humid tropics, however, is supported in the ancient record by examples with underlying mature paleosol profiles, chemical etching and lesser rounding of quartz grains, single populations of accessory minerals, downcurrent maturation, dissolution ghosts of labile grains, oversized pores filled with clay, and interstratified pelites composed of only kaolinite or illite. Post-depositional diagenesis also can contribute to maturation either with or without multicycling and may even produce pure, diagenetic quartz arenites in extreme cases. Accounting for the compositional maturity of ancient quartz arenites chemically seems paradoxical without something to stabilize land surface areas long enough to allow intense weathering. Biological crusts or microbial mats composed of complex communities of cyanobacteria, algae, and lichens are here proposed as the likely means of stabilization. Although most familiar today in arid regions, such crusts are known in practically all climatic zones. Apparently they developed early in Precambrian time from marginal marine or lacustrine stromatolites and mats and were the first life forms to invade land long before the advent of vascular land vegetation. [PUBLICATION ABSTRACT]
Keywords: QUARTZ; GEOLOGICAL TIME; GEOLOGY; Proterozoic; Silurian; Cambrian; Precambrian::Proterozoic; Докембрий::Протерозой; Paleozoic::Silurian; Палеозой::Кембрийская; Палеозой::Силурийская; Paleozoic::Cambrian